Keefektifan Perlakuan Air Panas terhadap Nematoda Ditylenchus destructor pada Umbi Bawang Putih - Heri Ahmadi; Supramana Supramana; Mohamad Rahmad Suhartanto (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2019)
The Effectiveness of Hot Water Treatment Against Nematode Ditylenchus destructor on Garlic BulbsThe high importation of garlic increases the risk of entry and spread of Ditylenchus to Indonesia. The hot water treatment (HWT) has the potential to be developed as an effective and safe method for elimination Ditylenchus in garlic. The aim of the current research was to examine effectiveness of HWT application on imported garlic to eliminated Ditylenchus. The research consisted of garlic sampling, nematode identification and determination of population abundance, and HWT. Samples were taken from traditional markets. The range of HWT temperature tested was 41, 43, 45, 47, 49, 51, 53, and 55 °C for 20 minutes and control. Optimization of treatment time was carried out at 49–51 °C for 5, 10, 15, 20, 25, 30 minutes and control. The results showed that based on morphological characters the parasitic nematodes that infect imported garlic from China were D. destructor. Nematode populations are varied in the sample, the highest number was 508 nematodes per 50 g of garlic. Hot water temperature at 41–51 °C did not affect the quality of garlic, and the temperature of 49–55 °C caused 100% nematode mortality. Hot water at 49 °C for 20–30 minutes or 51 °C for 20–25 minutes effectively eliminated Ditylenchus in garlic without affecting the garlic quality. The research confirmed the presence of D. destructor in imported garlic imported from China, so it is recommended to tighten inspection at a port of entry and monitoring its potential spread in Indonesia.